PENGARUH CASH FLOW, GROWTH OPPORTUNITIES, DAN LEVERAGE TERHADAP CASH HOLDING - Jasim, Theresia Yosita; Tjakrawala, F.X Kurniawan (Jurnal Paradigma Akuntansi, 2025)
This study aims to determine the effect of cash flow, growth opportunities and leverage on cash holding in consumer cyclicals and consumer non cyclicals companies listed on the Indonesia Stock Exchange in 2017-2021. The technique for selecting the sample in this study used a purposive sampling technique and 234 data were selected from 270 data. In this study the method used to analyze the data was multiple linear regression analysis to test the hypothesis and used SPSS software version 21 and Microsoft Excel 365 as the data processing application for this study. The results of this study indicate that cash flow has a significant positive effect on cash holdings. Growth opportunities have no significant negative effect on cash holdings. Meanwhile, leverage has a significant negative effect on cash holdings.